Consumer Protection in the Building Materials Sector from the Perspective of Contractor Business Actors Who Are Consumers - Effendy, Edrick Edwardina; Aditya, Galih Rangga (JURNAL AKTA, 2025)
As a developing country, construction services are essential to Indonesia's economic growth. Based on current conditions, consumer protection in Indonesia's construction/building materials sector still faces challenges such as low consumer awareness and weak supervision of business actors. This research aims to analyze how norms are implemented in the law of engagement between consumers and business actors in the building materials sector, the view of the law of engagement towards retail consumers of building materials or contractors, and how the law protects retail consumers of building materials who are also business actors. The research method used is the normative legal research method, which aims to identify legal rules, principles, and doctrines as answers to emerging legal problems. The results of this research explain that the construction services sector is regulated by various regulations, such as Law No. 2 of 2017 concerning Construction Services, which regulates responsibilities, quality standards, and protection mechanisms in construction services. In this context, contract law and consumer protection play a central role in ensuring justice and legal certainty, especially for consumers of building materials who act as business actors.  As a consumer, you have the right to clear information, product quality that meets standards, and security guarantees, as regulated in the Consumer Protection Law (UU No. 8 of 1999) and the Civil Code (Civil Code). On the other hand, business actors are obliged to ensure that the products sold are safe and fulfill the agreement. In implementing engagement legal norms, law enforcement involves mediation, arbitration, courts, and administrative and criminal sanctions.